(untitled) (Medico Legal Update, 2020)
Introduction: Physiotherapy is a healthcare profession that assesses, diagnoses, treats and works to prevent diseases and disability. Physiotherapy is a part of primary health care system. Every person has right to access to primary health care services. Physiotherapy has an important role in various illness and disorders but people are less aware about its benefits. Amongst these various diseases one is breast cancer. Physiotherapy has important role in treating the complications of Ca-breast. However there is limited research available on awareness of Physiotherapy intervention on post-operative Ca-Breast. Objective: To find the awareness of physiotherapy intervention in post-operative CA-Breast. To find awareness of Physiotherapy among Doctors. To find out the number of post-operative Ca-Breast subjects referred to Physiotherapy. To find the awareness of Physiotherapy intervention in post-operative Ca-Breast among medical doctors. Material and Methodology: Total 120 doctors were included in survey. The questionnaire were self- devised pre validated. A survey were conducted with clinical doctors. Questions were closed ended to prevent any statistical error. Result: In this survey we found that there are 50 percent doctors who are aware about physiotherapy and 50 percent are aware about physiotherapy intervention in individuals with Ca-breast. Conclusion: The study on Awareness of Various Aspects of Physiotherapy among Medical Residents. In this study identified a need for physiotherapists to educate medical residents about various fields of physiotherapy like community based rehabilitation and industrial health physiotherapy, their extensive role in each of the specialty, treatment modalities and evaluative procedures through continuing education programs.